African reckoning a quest for good governance - edited by Francis, M.Deng. (Washington, D.C Brookings Institution, 1998)
This book investigates how changing norms of sovereignty may promote better governance in Africa. It begins by tracing the evolution of the concept of sovereignty and how, in the post-Cold War era, sovereignty has been redefined to emphasize the responsibility of the state to manage conflict and protect human rights. African Reckoning includes assessments of how state actors in Africa measure up to the norms inherent in the notion of sovereignty as responsibility. The book also examines the question of accountability at the regional and international levels.
Includes bibliographical references and index.
Keywords: Conflict management--Africa.